Impact of heterogeneous reactions on stratospheric chemistry of the Arctic - Douglass, Anne R.; Stolarski, Richard S. (1989)
The possible depletion of ozone due to heterogeneous reactions occurring in Arctic polar stratospheric clouds (PSCs) is fundamentally different from the Antarctic situation. PSCs in the Arctic are relatively short-lived and occur over limited regions of the Arctic stratosphere. The Arctic situation is examined using a model which calculates photochemical processes as a function of longitude in air circulating with fixed velocity around the pole at fixed pressure level and latitude. The model allows sunlight to vary diurnally and PSCs to occur in specified subregions of the domain. Measurements of chemical species including HCl, ClO, NO2 and HNO3 downwind from a PSC should show obvious changes compared to measurements in air unaffected by clouds. These species concentrations are found to be sensitive to sticking coefficients, cloud characteristics including particle number density and surface area, and to the PSC exposure time.